Test Construction Practices: A Narrative Inquiry Among English Teachers in Bangladeshi Tertiary Education - Hossain, Ibrahim; Yesmen Chowdhury, Dr. Farzana (STAIN Majene, 2024)
Assessment is a crucial component of the teaching and learning process within any educational setting. Teacher-constructed achievement tests are used as the only means of assessment in many educational contexts. Such tests can measure the attainment of educational objectives, facilitate effective instruction, and provide positive washback. This research employs a narrative inquiry approach to explore the test construction practices and to identify the influencing factors that shape these practices. It explores the lived experiences of a group of novice and experienced English language teachers at the tertiary level in Bangladesh. Individual stories are analysed using Brown and Abeywickrama’s (2010) five language assessment principles. The findings of this study reveal a substantial gap between the principles of test construction and the actual practices and reveal that practices are predominantly shaped by institutional regulations rather than teachers' grasp of assessment theory and techniques. The findings of the study have implications for teachers in constructing practical tests, teacher trainers in designing training modules, and policymakers in developing appropriate assessment policies.